An efficient variable-node XFEM for modeling multiple crack growth: A Matlab object-oriented implementation. (February 2020) - Ding, Junlei; Yu, Tiantang; Yang, Yin; Bui, Tinh Quoc
Highlights: General structure of a Matlab object-oriented variable-node XFEM computer code for multiple crack growth is described. Local mesh refinement coupled with variable-node elements is used to enhance accuracy and save computational cost. Stability analysis is performed to determine the active crack tips. Domain form of integral is corrected when crack tip reaches the free boundary or another crack. A corrected coalescence algorithm is proposed. Abstract: We present a Matlab object-oriented implementation of an efficient variable-node extended finite element method (XFEM) for multiple crack growth simulation in brittle materials. To enhance the accuracy of the present method, not only the local mesh refinement strategy is used, but also the variable-node elements are adopted to directly link different scale elements, saving the computational cost. In order to efficiently conduct coalescence detection, a modification is also presented. A stability analysis is performed to determine active crack tips, and the crack length control scheme is employed to model multiple crack growth. Mesh is locally refined simultaneously with the extension of cracked area via a straightforward manner. A general computer program structure for the Matlab object-oriented programming code for the variable-node XFEM is described. All those desirable features of the present work are demonstrated through five numerical examples with branching in linear-elastic fracture mechanics. In addition, this work provides an efficient computer code written by Matlab programming language for computational fracture simulation, which is for educational and academic uses.